Analisis Sistem Akuntansi Pengeluaran Kas Pada PT PLN Persero Tiga Binanga - bayu wulandari bayu (Akuntansi Prima, 2022)
The accounting system is a procedure or steps for collecting information on company activities. A good accounting system is needed in a company, including a cash disbursement accounting system. Because cash disbursements are all operational and non-operational activities of a company that result in reduced finances in a company, so cash disbursements in a company are very important to pay attention to in order to know the financial condition of a company. the amount of money that is in a company, an accounting system is needed to summarize all company activities that involve reduced company cash. The cash disbursement accounting system makes it easier for a company to know and facilitate cash management in its company. The purpose of this study is to analyze the cash disbursement accounting system at PT PLN Persero ULP Tigabinanga. The type of research that will be used in this research is descriptive research, which is a research that is conducted to explain the accounting system for cash disbursements at PT PLN Persero ULP Tigabinanga.